SIFAT FISIK MINYAK ATSIRI DAUN PALA (Myristica fragrans Houtt) ACEH SELATAN - Rizki Damayanti; Cut Nurul Fahmi; Rustam Efendi (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2015)
Essential oils are oils derived from plants that are aromatic. Numeg leaves are part of plant that containing essential oil. Each of essential oils from different plants will have different physical properties. In this study, the essential oil is produced using steam distillation method. The purpose of this study was to determine the physical properties of essential oils of nutmeg leaves South Aceh. The physical properties of essential oils can be evaluated from the percentage of moisture content, ash content, aroma, color, and rendemen. The results showed that the essential oil of nutmeg leaves are pale yellow, has a characteristic smell of nutmeg, the percentage of moisture content and ash, viscosity, density is respectively 6.8%, 2.1%, 0.4% yield density, 3.8 P, 0576 g/cm3. The essential oil of nutmeg leaves South Aceh can be used as pharmaceuticals. But the density of leaf nutmeg oil does not comply with ISO Standard.